Characterization of male breast cancer: results of the EORTC 10085/TBCRC/BIG/NABCG International Male Breast Cancer Program. (28th October 2017) - Cardoso, F; Bartlett, J M S; Slaets, L; van Deurzen, C H M; van Leeuwen-Stok, E; Porter, P; Linderholm, B; Hedenfalk, I; Schröder, C; Martens, J; Bayani, J; van Asperen, C; et al.
Abstract: Background: Male breast cancer (BC) is rare, managed by extrapolation from female BC. The International Male BC Program aims to better characterize and manage this disease. We report the results of part I, a retrospective joint analysis of cases diagnosed during a 20-year period. Methods: Patients with follow-up and tumor samples, treated between 1990 and 2010, in 93 centers/9 countries. Samples were centrally analyzed in three laboratories (the United Kingdom, the Netherlands and the United States). Results: Of 1822 patients enrolled, 1483 were analyzed; 63.5% were diagnosed between 2001 and 2010, 57 (5.1%) had metastatic disease (M1). Median age at diagnosis: 68.4 years. Of 1054 M0 cases, 56.2% were node-negative (N0) and 48.5% had T1 tumors; 4% had breast conserving surgery (BCS), 18% sentinel lymph-node biopsy; half received adjuvant radiotherapy; 29.8% (neo)adjuvant chemotherapy and 76.8% adjuvant endocrine therapy (ET), mostly tamoxifen (88.4%). Per central pathology, for M0 tumors: 84.8% ductal invasive carcinomas, 51.5% grade 2; 99.3% estrogen receptor (ER)-positive; 81.9% progesterone receptor (PR)-positive; 96.9% androgen receptor (AR)-positive [ER, PR or AR Allred score ≥3]; 61.1% Ki67 expression low (<14% positive cells); using immunohistochemistry (IHC) surrogates, 41.9% were Luminal-A-like, 48.6% Luminal-B-like/HER-2-negative, 8.7% HER-2-positive, 0.3% triple negative. Median follow-up: 8.2 years (0.0–23.8) for all, 7.2 years (0.0–23.2), for M0, 2.6 years (0.0–12.7) for M1 patients. A significant improvement over time was observed in age-corrected BC mortality. BC-specific-mortality was higher for men younger than 50 years. Better overall (OS) and recurrence-free survival (RFS) were observed for highly ER+ ( P  = 0.001), highly PR+ ( P  = 0.002), highly AR+ disease ( P  = 0.019). There was no association between OS/RFS and HER-2 status, Ki67, IHC subtypes nor grade. Conclusions: Male BC is usually ER, PR and AR-positive, Luminal B-like/HER2-negative. Of note, 56% patients had T1 tumors but only 4% had BCS. ER was highly positive in >90% of cases but only 77% received adjuvant ET. ER, PR and AR were associated with OS and RFS, whereas grade, Ki67 and IHC surrogates were not. Significant improvement in survival over time was observed.